2001
DOI: 10.1099/00207713-51-2-303
|View full text |Cite
|
Sign up to set email alerts
|

Pyrobaculum oguniense sp. nov., a novel facultatively aerobic and hyperthermophilic archaeon growing at up to 97 degrees C.

Abstract: A novel hyperthermophilic, heterotrophic, rod-shaped archaeon was isolated from a terrestrial hot spring at Oguni-cho, Kumamoto Prefecture, Japan. T exhibited a close relationship to the sequences of Pyrobaculum aerophilum and Thermoproteus neutrophilus, which belong to the cluster of the genus Pyrobaculum. DNA-DNA hybridization analysis showed a low level of DNA similarity between TE7T and previously described Pyrobaculum species. As TE7 T is phenotypically and phylogenetically different from the other member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 34 publications
2
40
0
Order By: Relevance
“…P. oguniense (JCM10595 T ) was grown in MS medium at 90˚C and pH 7?0-7?5 as described previously (Sako et al, 2001). Aerobic batch cultures were grown in cotton-plugged 2 l Erlenmeyer flasks containing 1 l medium in an air bath rotary shaker (RGS-32.TT; Sanki Seiki, Osaka, Japan) with vigorous rotary shaking (100 r.p.m.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…P. oguniense (JCM10595 T ) was grown in MS medium at 90˚C and pH 7?0-7?5 as described previously (Sako et al, 2001). Aerobic batch cultures were grown in cotton-plugged 2 l Erlenmeyer flasks containing 1 l medium in an air bath rotary shaker (RGS-32.TT; Sanki Seiki, Osaka, Japan) with vigorous rotary shaking (100 r.p.m.).…”
Section: Methodsmentioning
confidence: 99%
“…Under anaerobic conditions, this organism grows with elemental sulfur, thiosulfate, glutathione (oxidized form) or L-cystine as terminal electron acceptor (Sako et al, 2001). From the aspect of respiration, the genus Pyrobaculum is uniquely variable among the hyperthermophilic archaea, which may be closest to the common ancestor of all organisms; P. aerophilum is not only a microaerophile but also a nitrate, nitrite, thiosulfate, arsenate and selenite reducer (Völkl et al, 1993;Huber et al, 2000); Pyrobaculum islandicum reduces sulfur and iron(II) compounds (Huber et al, 1987;Kashefi & Lovely, 2000;Vargas et al, 1998); Pyrobaculum organotrophum reduces sulfur compounds (Huber et al, 1987); Thermoproteus neutrophilus, which is classified in the genus Thermoproteus although the phylogenetic analysis of 16S rDNA indicated that it should be reclassified as a Pyrobaculum species (Ito et al, 1998), is a sulfur reducer (Fischer et al, 1983); Pyrobaculum arsenaticum is arsenite reducer .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, hyperthermophilic archaea, capable of growing under an atmosphere of air such as Acidianus (Segerer et al, 1986;Zillig et al, 1986), Sulfurisphaera (Kurosawa et al, 1998), Sulfolobus (Zillig et al, 1980;Grogan et al, 1990;Jan et al, 1999;Suzuki et al, 2002) and Pyrobaculum (Sako et al, 2001;Amo et al, 2002) species isolated in terrestrial hot springs, have been never isolated from deep-sea hydrothermal environments. However, we have recently isolated strictly aerobic thermophiles, Marinithermus hydrothermalis strain T1 T and Rhodothermus sp.…”
mentioning
confidence: 99%
“…The two former strains were grown in DSMZ medium 1090, as described above. Cells of P. oguniense were grown in DSMZ medium 390 (49). In all cases, the pH value was adjusted to about 7.…”
Section: Methodsmentioning
confidence: 99%